Ultrasonic flaw detectors. Estimation of the measurement uncertainty by calibrated attenuator\gain - Panjiev Ulugbek; Muminov Najmiddin Shamsiddinovich (Genius Journals, 2024)
There are technical specifications such as linearity accuracy, gain and also material velocity which is estimated during the calibration of ultrasonic flaw detectors. One of these main parameters is the gain. This article considers the assessment for the measurement uncertainty by calibrated attenuator\gain of ultrasonic flaw detectors, which is used in the ultrasonic method of non-destructive testing, using ultrasonic tester
Keywords: Non-destructive testing; ultrasonic method; flaw detector